Agrobiodiversity and climate change: what do students need to know? - Rudebjer, P.G.; Baidu-Forson, Joseph Jojo; Schagen, Boudy van; Jarvis, A.; Staver, Charles; Hodgkins, T. (World Agroforestry Centre, 2008)
Key note paper presented at 2nd ANAFE International Symposium: ‘Mainstreaming climate change into agricultural education: tools, experiences and challenges’, Malawi, 2008. The paper informs that adaptation of production systems to climate change requires human capacity in agricultural biodiversity but a 2007 survey in African universities showed that education in this area is weak or absent. The authors argue that role of agricultural biodiversity in adaptation to climate change should be better understood, and that universities should seek to develop such competencies in their students. Universities should review curricula to include agricultural biodiversity dimensions through innovative, experiential teaching methods and active student participation.